KONSEP PEMBELAJARAN DIFERENSIASI BERBASIS KEARIFAN LOKAL: SEBUAH KAJIAN LITERATUR DENGAN KONTEKS MADRASAH DI LAMPUNG - Umurohmi, Ulfah (LPPM Institut Agam Islam Nahdlatul Ulama (IAINU) Kebumen, 2023)
This article aims to study the concept of differential learning based on local wisdom in the context of madrasah education in Lampung. Given the rich background of local wisdom in Lampung, the study was conducted through a literature review with a qualitative descriptive approach. Data analysis techniques involve the identification, categorization, and synthesis of information from various relevant literary sources. This allows researchers to understand how local wisdom can be integrated into differential learning in the madrasah. The results of this study show that differential learning in the madrasah with an instructional approach is adapted to the individual needs of students, taking into account the diversity of student background and ability. The local wisdom and traditions of Lampung, such as listener pii and samali sambayan, give deep values to the learning process. Strategies to integrate local wisdom into learning include the use of relevant media, materials, methods, and evaluations. The Madrasah in Lampung, by combining local wisdom and differentiation approaches, has the potential to improve the quality and relevance of education for students in the region